2021
DOI: 10.3390/pathogens10050627
|View full text |Cite
|
Sign up to set email alerts
|

From Coxiella burnetii Infection to Pregnancy Complications: Key Role of the Immune Response of Placental Cells

Abstract: The infection of pregnant animals and women by Coxiella burnetii, an intracellular bacterium, compromises both maternal health and foetal development. The placenta is targeted by C. burnetii, as demonstrated by bacteriological and histological evidence. It now appears that placental strains of C. burnetii are highly virulent compared to reference strains and that placental injury involves different types of placental cells. Trophoblasts, the major placental cells, are largely infected by C. burnetii and may re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1
1
1

Relationship

4
3

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 77 publications
(107 reference statements)
0
11
0
Order By: Relevance
“…It was previously reported that many cell types, including myeloid cells [47,48], trophoblasts [4,49], lung cells [50,51], and adipocytes [5] dense circular structures, with diameters ranging from 250 nm to 700 nm dispersed in the cell cytoplasm, corresponding to the morphology and size of C. burnetii as previously described [54].…”
Section: Selection Of the Bewo Cell Line As An Appropriate Cellular M...mentioning
confidence: 76%
See 1 more Smart Citation
“…It was previously reported that many cell types, including myeloid cells [47,48], trophoblasts [4,49], lung cells [50,51], and adipocytes [5] dense circular structures, with diameters ranging from 250 nm to 700 nm dispersed in the cell cytoplasm, corresponding to the morphology and size of C. burnetii as previously described [54].…”
Section: Selection Of the Bewo Cell Line As An Appropriate Cellular M...mentioning
confidence: 76%
“…It was previously reported that many cell types, including myeloid cells [47,48], trophoblasts [4,49], lung cells [50,51], and adipocytes [5] are susceptible to C. burnetii infection. To conduct our study, it was first necessary to select a cellular model with high expression of E-cad.…”
Section: Selection Of the Bewo Cell Line As An Appropriate Cellular M...mentioning
confidence: 99%
“…It was previously reported that many cell types, including myeloid cells [ 51 , 52 ], trophoblasts [ 4 , 53 ], lung cells [ 54 , 55 ], and adipocytes [ 5 ] are susceptible to C . burnetii infection.…”
Section: Resultsmentioning
confidence: 99%
“…They are mostly asymptomatic (60%), while 40% develop an acute Q fever and 2% progress to a persistent focal infection [ 1 ]. During pregnancy, exposure to C. burnetii increases the risk of developing acute Q fever but the illness is most often asymptomatic, which delays a diagnosis based on serology [ 2 , 3 , 4 , 5 , 6 ]. Hence, obstetrical complications including miscarriage, malformations, growth retardation, premature delivery and foetal death may occur [ 7 , 8 , 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…C. burnetii infects domestic ruminants, leading to infertility, endometritis and mastitis, and obstetrical complications such as still birth and abortion (90%) [ 12 , 13 ]. The pathogenesis of C. burnetii obstetrical complications in animal models results from placental infection and the recruitment of immune cells [ 2 , 3 , 13 , 14 ]. The role of C. burnetii organisms is counteracted by the benefits of antibiotic treatments and the vaccination strategy that have been proposed to reduce abortion rates [ 14 , 15 ].…”
Section: Introductionmentioning
confidence: 99%